Speculations VI - Gironi, Fabio, 1983-; Austin, Michael; Jackson, Robert (Punctum Books, 2015)
"In this sixth issue of Speculations, a serial imprint created to explore post-continental philosophy and speculative realism, a wide range of contemporary philosophical issues pertaining to the contemporary philosophical scene is touched upon, from the continental realism of Tristan Garcia, Graham Harman and Quentin Meillassoux to the 'new realism' of Maurizio Ferraris, from Lacanian and Laurellian speculations to the synthetic philosophy of Fernando Zalamea's mathematics"--